Intelligent transport algorithms for calculating qualitative road traffic parameters - Chua, Delvin Ming Rui (Nanyang Technological University, 2024)
With the increase in human population as well as traffic road usage across the globe, land scarcity, especially in the context of Singapore, has become a major issue that cannot be overlooked. Technology is also constantly improving, becoming more efficient and effective in our everyday lives.